Periods of sourgrass interference in the soybean - Piazentine, Ana Eliza; César Carrega, Willians; Lopes Bacha, Allan; Luis da Costa Aguiar Alves, Pedro (Revista Ciência Agronômica, 2024)
Sourgrass (Digitaria insularis) is one of the principal weeds in Brazil, and there are reports of its being glyphosate-resistant. The aim of this study was to determine the coexistence period of the TMG7063 IPRO soybean cultivar with a weed community predominated by D. Insularis, with no negative interference on final production (period prior to interference - PPI), as well as to determine the period for which the crop must remain free of such interference (total period of interference prevention) in Brazil. The coexistence and control periods under study were 15, 30, 45, 60, 75, 90, 105, and 120 days after sowing (DAS) the soybean, with the experiment arranged in a randomized block design with four replications. At the end of each coexistence period and at the end of the control-period experiment (single collection), there was an increase in weed density, dry matter, and the relative importance of D. insularis as the coexistence period increased.  The number of pods was reduced from 87 (from 120 DAS in the control) to 49 (from 75 DAS for coexistence), and maximum yield was reduced from 5,551.3 kg ha-1 (from 120 DAS in the control) to 3,998.6 kg ha-1 (from 60 DAS for coexistence) due to coexistence with the weed community. The PPI was estimated at nine DAS, with losses of 5.0%. It can be concluded that a weed community predominated by D. insularis reduces soybean yield by up to 59.3%. The ‘TMG 7063 IPRO’ soybean can coexist with a weed community predominated by D. insularis for up to nine days after sowing and tolerate a loss in yield of up to 5%.